ANALISIS HUBUNGAN KARAKTERISTIK DAN PERILAKU WIRAUSAHA PENJUAL PECEL SEMANGGI DI KAMPUNG SEMANGGI KOTA SURABAYA - Dacosta, Jose Inaksio; Indah, Pawana Nur; Sudiyarto, Sudiyarto (Agridevina : Berkala Ilmiah Agribisnis, 2021)
This study aims to analyze the entrepreneurial behavior of semanggi pecel sellers in Semanggi Village, Surabaya City. The subject of this research is clover pecel traders, both street vendors and traders who settled somewhere. Changes in behavior are influenced by one's internal and environmental factors in which a person interacts socially (Dirlanudin, 2010). The sample of this study was 37 respondents. The analytical method used is Spearman Rank correlation analysis with the analysis tool is SPSS. Careful entrepreneurial behavior includes knowledge, attitudes, and skills. Each entrepreneurial behavior was measured using a questionnaire and each behavior was represented by 20 questions. This study concludes that the calculated average of the score of semanggi pecel entrepreneurial behavior is 226.92 which means it is in the high category. High entrepreneurial behavior as many as 31 people with 83.78 percent, very high as many as 5 people with 13.51 percent and as many as one person 2.70 percent. DOI : https://doi.org/10.33005/adv.v10i2.2912